Thermal properties of novel sandwich roof panel made of basalt fiber reinforced plastic material. (15th July 2022) - Su, Bo; Zhang, Tianyu; Chen, Shixing; Hao, Jianming; Zhang, Rui
Abstract: The design of roof panels faces practical challenges, such as thermal property requirements. In this study, following the function-integrated design concept, a novel Basalt Fiber Reinforced Plastic (BFRP) sandwich roof panel is presented. A series of experiments, together with theoretical and numerical analysis are performed to investigate their thermal performance as roof panels. The main works and results are: (i) According to Calibration Hot Box (CHB) results, for BFPR panel with 70 mm thickness, the heat transfer coefficients of 3 specimens infilled with XPS, PU or Rock wool are 0.55 W · m - 2 · K - 1, 0.40 W · m - 2 · K - 1 and 0.60 W · m - 2 · K - 1 respectively, which well match with theoretical and numerical results. (ii) Analytical model and Finite element (FE) method are used to calculate heat transfer coefficients of BFPR panels with five different thickness (60 mm, 70 mm, 80 mm, 90 mm, 100 mm), which offer choice to adapt to thermal property requirements for different thermal regions defined by the code. (iii)Comparing with some newly developed SIPs in literatures, BFRP STPs have better thermal performance than plywood-faced sandwich and bamboo-wood based shear walls with similar thickness. (iv)According to temperature distribution pattern on BFRP panel surface, thermal bridge was seen occurring at the edge of BFPR square tubes. However, by steady-state analysis, heat flow passing by edge of BFRP square tubes occupies 5.82%–10.17% of that of the total section. The main contributions of this paper thus lie in three aspects: (1) Proposing a novel structural insulated panels (SIPs), utilizing BFPR as face and rib for sandwich structure, and isolation materials as core materials, which are specially designed and manufactured as building roof panels; (2) Thermal properties of the BFRP SIPs are systematically studied, which shows BFRP SIPs have excellent thermal properties with low heat transfer coefficient and thermal bridge effect. (3) Effect of thickness on thermal conductivity is investigated by numerical simulation, and proper thickness of BFRP SIPs are recommended to meet the thermal property requirements for different thermal regions in the code. Highlights: Novel structural insulated panels (SIPs) utilizing basalt fiber reinforced polymers (BFPR) are presented as roof slab. Results showed BFRP SIPs have excellent thermal properties with low heat transfer coefficient and thermal bridge effect. Thickness effect on thermal conductivity of BFRP SIPs and proper design for different thermal regions are proposed.